2010
DOI: 10.1038/npp.2010.195
|View full text |Cite
|
Sign up to set email alerts
|

The Presynaptic Component of the Serotonergic System is Required for Clozapine's Efficacy

Abstract: Clozapine, by virtue of its absence of extrapyramidal side effects and greater efficacy, revolutionized the treatment of schizophrenia, although the mechanisms underlying this exceptional activity remain controversial. Combining an unbiased cheminformatics and physical screening approach, we evaluated clozapine's activity at 42350 distinct molecular targets. Clozapine, and the closely related atypical antipsychotic drug olanzapine, interacted potently with a unique spectrum of molecular targets. This distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 60 publications
8
74
0
Order By: Relevance
“…Hence, CLZ and other atypical antipsychotic drugs (but not classical dopamine D2 blockers) share the ability to increase DA release in rodent mPFC through 5-HT 1A R activation (Bortolozzi et al, 2007;DiazMataix et al, 2005;Ichikawa et al, 2001;Li et al, 2009;Rollema et al, 1997Rollema et al, , 2000, an effect depending on the exclusive activation of 5-HT 1A R in mPFC as observed in KO mice (Bortolozzi et al, 2007Diaz-Mataix et al, 2005). These results also agree with a recent report indicating that CLZ's ability to normalize NMDA-R hypofunction in vivo depends on an intact presynaptic serotonergic function and that 5-HT 2A R are not essential for CLZ reversal of PCP-induced disruption of sensory-motor gating (Yadav et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Hence, CLZ and other atypical antipsychotic drugs (but not classical dopamine D2 blockers) share the ability to increase DA release in rodent mPFC through 5-HT 1A R activation (Bortolozzi et al, 2007;DiazMataix et al, 2005;Ichikawa et al, 2001;Li et al, 2009;Rollema et al, 1997Rollema et al, , 2000, an effect depending on the exclusive activation of 5-HT 1A R in mPFC as observed in KO mice (Bortolozzi et al, 2007Diaz-Mataix et al, 2005). These results also agree with a recent report indicating that CLZ's ability to normalize NMDA-R hypofunction in vivo depends on an intact presynaptic serotonergic function and that 5-HT 2A R are not essential for CLZ reversal of PCP-induced disruption of sensory-motor gating (Yadav et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…Time between injections was 10-12 min. The dose of CLZ was chosen from the literature owing to its ability to antagonize behavioral effects of NMDA-R antagonists (Bradford et al, 2010;Gleason and Shannon, 1997;Mutlu et al, 2011;Scorza et al, 2010;Yadav et al, 2011).…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…58 Alternatively, recently introduced genetically modified mice with selective 5-HT 1A auto-or heteroreceptor inactivation could be used to dissect the relative contribution of these receptor subpopulations in PPI regulation. 59,60 Such experiments might also further clarify the marked differences between C57Bl/6 mice and Balb/c mice.…”
Section: ■ Discussionmentioning
confidence: 97%
“…Response to dizocilpine ↑ Figure 1d Response to amphetamine ↑ Figure 1e Sensorimotor gating Prepulse inhibition ↓ Figure 1a and b Attention Latent Inhibition X Figure 2e Cognitive function Novel object recognition memory (short term) ↓ Figure 2a Novel object recognition memory (long term) ↓ Figure 2b Contextual fear memory ↓ Figure 2c Cued fear memory ↓ Figure 2d Social memory ↓ Figure 1h Social interaction Sociability ↓ Figure 1f Juvenile conspecific ↓ Supplementary Figure S1f Sleep architecture Wakefulness ↑ Figure 3a and c NREM sleep ↓ Figure 3a and d REM sleep - Figure 3a and e REM latency ↓ Figure 3b for 5-HT 2B receptors (eg, aripiprazole, cariprazine) (Kiss et al, 2010;Shapiro et al, 2003). Notably, it was recently shown that the efficacy of clozapine, but not haloperidol, is diminished in Pet1 −/− mice that lack 5-HT neurons, and thus depends on an intact presynaptic serotonergic system (Yadav et al, 2011). Given that many marketed atypical antipsychotic drugs present high affinity for 5-HT 2B receptors (Shapiro et al, 2003) and that these receptors are expressed in 5-HT neurons (Diaz et al, 2012), our findings bear broader significance for the elucidation of the effects of these drugs in the treatment of psychotic disorders.…”
Section: Per Group) In the Latent Inhibition (Li) Paradigm (E) LI Wmentioning
confidence: 99%
“…Sensorimotor gating was assessed as previously described (Yadav et al, 2011). PPI was indexed by the percentage inhibition of the startle response at each level of prepulse intensity by using the following formula: % PPI = ((mean reactivity on pulsealone trials − mean reactivity on prepulse-pulse trials)/mean reactivity on pulse-alone trials) × 100%.…”
Section: Ppi Of Acoustic Startlementioning
confidence: 99%